Historiographical Considerations about Wall Decoration and illusionistic Painting: From Italy and European Peripheries to the Spanish and Iberoamerican Context - Jaquero Esparcia, Alejandro (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2023)
The aim of this paper is to study in detail the historical discourse of wall decoration, especially the illusionistic architectonical painting. Although this ornamental aspect has been used since the Classical Antiquity, its analysis was the runner-up in locations where wall painting studies and architectural ensembles got their turn in the spotlight. In the middle of the 20th century, particularly at the beginning of the Early Modern Age, we can find the first publications that vindicated the originality of these works specially its progress into the Italian space. This contribution suggests a chronological itinerary since The Modernity to the Western Europe outlook, and the reception of this experience in Spain and its derivations to the Ibero-american context. Likewise, we try to highlight the importance of the interdisciplinary work, the new academic research proposals, the role of the TICS in its preservation and divulgation, among other points of view that enrich our knowledge about wall decorations.
Keywords: wall painting; modern period; pictorial decoration; illusionistic painting; Quadrattura; cultural heritage